Antimicrobial and Phylogenomic Characterization of Bacillus cereus Group Strains Isolated from Different Food Sources in Italy - Donatella Farina; Angelica Bianco; Viviana Manzulli; Stefano Castellana; Antonio Parisi; Marta Caruso; Rosa Fraccalvieri; Luigina Serrecchia; Valeria Rondinone; Lorenzo Pace; Antonio Fasanella; Valerio Vetritto; et al. (MDPI AG, 2024)
Background: Bacillus cereus is a widespread environmental Gram-positive bacterium which is especially common in soil and dust. It produces two types of toxins that cause vomiting and diarrhea. At present, foodborne outbreaks due to Bacillus cereus group bacteria (especially Bacillus cereus sensu stricto) are rising, representing a serious problem in the agri-food supply chain. Methods: In this work, we analyzed 118 strains belonging to the Bacillus cereus group, isolated from several food sources, for which in vitro and in silico antibiotic resistance assessments were performed. Results: Many strains showed intermediate susceptibility to clindamycin, erythromycin, and tetracycline, suggesting an evolving acquisition of resistance against these antibiotics. Moreover, one strain showed intermediate resistance to meropenem, an antibiotic currently used to treat infections caused by Bacillus cereus. In addition to the phenotypic antimicrobial resistance profile, all strains were screened for the presence/absence of antimicrobial genes via whole-genome sequencing. There was inconsistency between the in vitro and in silico analyses, such as in the case of vancomycin, for which different isolates harbored resistance genes but, phenotypically, the same strains were sensitive. Conclusions: This would suggest that antibiotic resistance is a complex phenomenon due to a variety of genetic, epigenetic, and biochemical mechanisms.